2018
DOI: 10.1371/journal.ppat.1007398
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 capsids from B27/B57+ elite controllers escape Mx2 but are targeted by TRIM5α, leading to the induction of an antiviral state

Abstract: Elite controllers (ECs) are a rare subset of HIV-1 slow progressors characterized by prolonged viremia suppression. HLA alleles B27 and B57 promote the cytotoxic T lymphocyte (CTL)-mediated depletion of infected cells in ECs, leading to the emergence of escape mutations in the viral capsid (CA). Whether those mutations modulate CA detection by innate sensors and effectors is poorly known. Here, we investigated the targeting of CA from B27/B57+ individuals by cytosolic antiviral factors Mx2 and TRIM5α. Toward t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 68 publications
1
30
1
Order By: Relevance
“…Furthermore, the HIV-restrictive effect of priming was substantially reduced (albeit not eliminated) in TRIM5 knockout THP-1 cells ( Fig 6F ) and was restored following TRIM5 add-back (Figs 6G and S4D ), thus establishing that the effect is at least partially TRIM5-dependent. These results mirror those reported by Merindol et al [ 14 ], who found that prior exposure of macrophages to TRIM5-restricted HIV-1 isolates from an elite controller population conferred protection against infection by wild type HIV-1 in a manner requiring TRIM5, UBC13, and TAK1. Since the ability of human TRIM5 to restrict HIV-1 in THP-1 cells is only effective secondarily to priming with a restricted virus, we refer to this effect as s econdary T RIM5 r estriction (STR).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the HIV-restrictive effect of priming was substantially reduced (albeit not eliminated) in TRIM5 knockout THP-1 cells ( Fig 6F ) and was restored following TRIM5 add-back (Figs 6G and S4D ), thus establishing that the effect is at least partially TRIM5-dependent. These results mirror those reported by Merindol et al [ 14 ], who found that prior exposure of macrophages to TRIM5-restricted HIV-1 isolates from an elite controller population conferred protection against infection by wild type HIV-1 in a manner requiring TRIM5, UBC13, and TAK1. Since the ability of human TRIM5 to restrict HIV-1 in THP-1 cells is only effective secondarily to priming with a restricted virus, we refer to this effect as s econdary T RIM5 r estriction (STR).…”
Section: Resultssupporting
confidence: 90%
“…TRIM5 can stimulate innate immune signaling in response to its recognition of restriction-sensitive retroviral cores [ 12 14 ]. Our results showing a requirement for autophagy factors in activation of these same immune pathways in response to TRIM5 over-expression suggested that autophagy factors may also contribute to TRIM5-dependent signaling in response to retroviral capsid.…”
Section: Resultsmentioning
confidence: 99%
“…The role of human TRIM5α in suppression of HIV-1 has been controversial, in part because early studies suggested no restriction of laboratory strains of HIV-1. However, recent studies suggest that cytotoxic T lymphocyte (CTL)-selected HIV-1 isolates from so-called ‘elite controllers’ are susceptible to restriction by human TRIM5α 38 , and genetic studies suggest that human polymorphisms in TRIM5 impact disease progression 13 . To further examine whether TRIM5α in human cells restricts flavivirus replication, we first immunoprecipitated LGTV NS2B/3 following ectopic expression in unmodified HEK293 cells which revealed an interaction with endogenous TRIM5α (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TRIM5α restriction acts at the pre-integration phase of the life-cycle, displays cross-talk with the adaptive immune response and may negatively affect viral RC. There is evidence to support this proposition, as HIV-1 CTL escape variants display increased sensitivity to restriction by TRIM5α [107]. The RC of these escape variants may be further reduced, given the functional constraints on capsid structure [108].…”
Section: Conclusion: Possible Causal Factors Which Promote Hiv-2 Disementioning
confidence: 97%
“…There is evidence to support this proposition, as HIV-1 CTL escape variants display increased sensitivity to restriction by TRIM5α [107]. TRIM5α restriction acts at the pre-integration phase of the life-cycle, displays cross-talk with the adaptive immune response and may negatively affect viral RC.…”
Section: Conclusion: Possible Causal Factors Which Promote Hiv-2 Disementioning
confidence: 99%